Strategi Kepala Madrasah dalam Membangun Budaya Religius di MAN 1 Musi Banyuasin - Jumiati Jumiati; Muhammad Win Afgani; Afriantoni Afriantoni (Departement of Mathematics Education, 2024)
This study aims to describe the role of Madrasah Principal in building a religious culture MAN 1 Musi Banyuasin . This research uses descriptive qualitative research. data collection techniques used by researchers are observation, interviews, and documentation. The subjects used in the study were the Head of Madrasah, teachers and students. Based on the results of the study, it can be concluded that the role of the Madrasah Principal used in building a religious culture in MAN 1 Musi Banyuasin is to apply the 5S (culture of smile. greeting, greeting, politeness and courtesy), conducting morning apples by reading and memorizing Tahfidz Al-Qur'an, before starting learning to get used to reading prayers before learning, performing dhuha and dhuhur prayers together, reading and memorizing yasin and infaq every Friday with the aim of instilling the values contained in the Al-Qur'an to students in implementing a religious culture,